2018
DOI: 10.1137/17m1116349
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Estimation via Nonanticipative Rate Distortion Function and Applications to Time-Varying Gauss--Markov Processes

Abstract: In this paper, we develop finite-time horizon causal filters using the nonanticipative rate distortion theory. We apply the developed theory to design optimal filters for time-varying multidimensional Gauss-Markov processes, subject to a mean square error fidelity constraint. We show that such filters are equivalent to the design of an optimal {encoder, channel, decoder}, which ensures that the error satisfies a fidelity constraint. Moreover, we derive a universal lower bound on the mean square error of any es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 27 publications
1
58
0
Order By: Relevance
“…It is well-known that the optimization problem of (7) is convex with respect to the set of test channels P(dy n ||x n ) that satisfy the average (over time) MSE distortion, for D ∈ (0, D max ) ⊆ (0, ∞), and there exists an optimal solution characterizing it under general source distributions and distortion functions (e.g., [10]). By [8,Theorem 4.1], the optimal "test channel" corresponding to R 0,n (D) is of the form…”
Section: Problems Statement and Preliminary Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well-known that the optimization problem of (7) is convex with respect to the set of test channels P(dy n ||x n ) that satisfy the average (over time) MSE distortion, for D ∈ (0, D max ) ⊆ (0, ∞), and there exists an optimal solution characterizing it under general source distributions and distortion functions (e.g., [10]). By [8,Theorem 4.1], the optimal "test channel" corresponding to R 0,n (D) is of the form…”
Section: Problems Statement and Preliminary Resultsmentioning
confidence: 99%
“…Note that by choosing ∆ as in (32), we ensure that ∆ Λ. We wish to remark that the extension of Theorem 3 and Proposition 1 to the non-asymptotic regime appears in [8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be shown following, for instance, the techniques of [ 23 ]. By the structural properties of the test channel derived in ([ 24 ], Section 4), if the source is first-order Markov, i.e., with distribution , the test channel distribution is of the form . Finally, combining this structural result, with ([ 25 ], Theorem 1.8.6), it can be shown that if is Gaussian then a jointly Gaussian process achieves a smaller value of the information rates, and if is Gaussian and Markov, then the infimum in ( 26 ), ( 28 ) and ( 30 ) can be restricted to test channel distributions which are Gaussian, of the form .…”
Section: Lower Boundsmentioning
confidence: 99%